Two Cases of Gastric Volvulus in Neonates - Min Yeong Kim; Moon Sung Park; Jang Hoon Lee (Korean Society of Neonatology, 2021)
Gastric volvulus in neonates is an extremely uncommon disorder, which is challenging to diagnose because of its non-specific clinical manifestations. Early diagnosis of gastric volvulus is important to avoid life-threatening complications, such as gastric ischemia, necrosis, and perforation. A definitive diagnosis could be made with radiological upper gastrointestinal series. In this report, we present two cases of neonate gastric volvulus, which were confirmed by radiological upper gastrointestinal series, and the patients underwent surgical treatment.